RANCANG BANGUN APLIKASI MANAJEMEN SIMPATISAN SEBAGAI OPTIMALISASI PEMENANGAN PEMILU LEGISLATIF - Tabrani, Ahmad; Fudoli, Fudoli (LP2M Institut Informatika Dan Bisnis Darmajaya, 2024)
In the effort to enhance the effectiveness and efficiency of political campaigns for legislative elections, the development of information technology plays a critical role. This research focuses on designing and developing a supporter management application specifically tailored to assist legislative candidates in managing and analyzing their supporter data. The application is equipped with key features such as supporter registration, coordinator management across various administrative levels (RT, RW, District), automated WhatsApp messaging for direct communication and as a form of appreciation, and a quick count feature to facilitate vote tallying. Additionally, the application offers comprehensive data analysis capabilities, allowing legislative candidates to understand supporter characteristics based on various categories such as age, occupation, and education level. This analysis feature is crucial for formulating more effective and targeted campaign strategies. The development method employed is the waterfall method, which includes stages of requirements analysis, system design, implementation, testing, and maintenance. This application has been used by legislative candidates in the DPRD of Tangerang Regency in the 2024 local elections and has shown positive results by enhancing supporter engagement and loyalty through structured and systematic communication. The application is expected to be an effective and reliable tool in supporting legislative election campaign strategies, contributing significantly to a more transparent and participatory democratic process